Free vibrations of laminated composite beams with multiple edge cracks: Numerical model and experimental validation. (August 2019) - Kahya, Volkan; Karaca, Sebahat; Okur, Fatih Yesevi; Altunışık, Ahmet Can; Aslan, Mustafa
Highlights: A finite element-based model for analysis of laminated composite beams including non-propagating edge cracks is developed. A damage extent coefficient is defined to introduce the damages within the laminated composite beam. The method provides a simple and quick way for determining of natural frequencies and mode shapes of the laminated composite beams with multiple transverse cracks. The method can also be used for the composite beams with any other type of damage such as delamination, low-velocity induced damage. The method can be integrated by an optimization algorithm for damage detection in laminated composite beams. Abstract: Free vibration analysis of laminated composite beams including open transverse cracks is presented by using a shear-deformable thirteen degrees-of-freedom finite element model, which considers extension-twist, bending-twist and bending-extension couplings, and the Poisson's effect. Lagrange's equation is employed to derive the equations of motion. Trial functions are selected as cubic Lagrange polynomials for deflections while quadratic for the others in derivation of element mass and stiffness matrices. Damage is introduced into the beam by reducing stiffness of elements within damaged zone. Comparisons are made with the available literature to show the present element's accuracy. Experimental validation is also performed with through ambient vibration tests on a cantilever laminated composite beam under six damage scenarios. According to the results, the methodology presented in this study provides a simple and quick way in a sufficient accuracy to determine the natural frequencies and mode shapes of laminated composite beams with open transverse non-propagating edge cracks.